Dinamika Konsepsi Penguasaan Negara Atas Sumber Daya Alam - Redi, Ahmad (Mahkamah Konstitusi Republik Indonesia, 2015)
Discourse concerning state control concept on natural resources in Article 33 clause (3) of the 1945 Constitution is very dynamic. Such dynamic can be seen on a variety of conceptions of state control rights on natural resources formulated in various acts in natural resources area. Lack of single concept on ‘state control right’ will impact to unfavorable situation where natural resources shall escape from conception of state control right and into control not by the state. The Constitutional Court as the Guardian and Interpreter of the Constitution has a significant role to ascertain that an act in natural resources area really adopt the principle of state control on natural resources in Indonesia. This article analyzes on dynamics of conception of state control on natural resources in various acts and the role of the Constitutional Court in guarding and interpreting acts in natural resources in order to be in accordance with Article 33 clause (3) of the 1945 Constitution. From the result of analysis a conclusion is achieved that there are many different concepts of state control on natural resources in various acts in natural resources area. The Constitutional Court indeed has made interpretation on state control right. In order to make the conception stronger it is necessary to have an act in natural resources area as instruction of Article 33 clause (5) of the 1945 Constitution that further provisions of Article 33 shall be regulated by an act. Moreover, DPR (The House of Representatives) and the Government have to make certain or definite the concept of state control right in every draft bill of natural resources area so that liberalism and capitalism stream will not erode the principle of state control right.